Childhood violence experience interacts with BDNF Val158Met polymorphism and modify internet addiction risk. (1st June 2022) - Chuprova, N.; Merkulova, T.; Solovieva, M.; Nikolishin, A.; Trusova, A.; Grechany, S.; Soldatkin, V.; Yakovlev, A.; Ponizovsky, P.; Ilyuk, R.; Egorov, A.; Krupitsky, E.; et al.
Abstract : Introduction: Internet-addiction (IA) is one of the most common non-chemical (or behavioral) addictions with genetic impact and substantial effects of psychological and personality characteristics, taking into account the childhood traumatic experience. Gene-environment interactions (GxE) may substantially impact on the risk of Internet-addiction (IA). Objectives: Aim: to test the associations between the functional polymorphism rs6265 (Val66Met) in brain-derived neurotrophic factor (BDNF) gene, affecting BDNF function, and childhood traumatic experience and their GxE interactions with IA risk. Methods: In total 456 participants were screened with Chinese Internet Addiction Scale (CIAS) to cut a cohort on two groups: IA (CIAS total score ≥ 65, n=100) and controls (CIAS total score less 64, n=356). The Adverse Childhood Experiences International Questionnaire (ACE-IQ) was used to assess childhood traumatic experience using its main domains: parents (P), family (F), abuse (A) and violence (V). BDNF Val158Met polymorphism was detected by RT-PCR. Results: Logistic regression revealed associations of P scores with increased IA risk only after adjustment for sex and age (p=0.01, OR=1.166, 95%CI[1.038-1.309]) and V scores with decreased IA risk (p=0.000, OR=0.799, 95%CI [0, 233;0, 744] only before adjustment. No associations of F and A with IA risk were found. BDNF Val158Met per se was not associated with IA risk, but significant effect of interaction V score*BDNF rs6265 CC on IA risk in "protective" manner was revealed (р=0.039, OR=0.873, 95%CI[0.768-0.993]) in a model adjusted for sex and age. Conclusions: Childhood violence experience interacts with BDNF Val158Met polymorphism and CC (ValVal) genotype may be possibly protective factor decreasing the internet addiction risk Disclosure: This work was carried out with the financial support of the Russian Foundation for Basic Research: RFBR grant # 18-29-22079